(untitled) (REMUNOM, 2025)
Objective: This study aimed to report the experience of physical therapy students and residents in cardiometabolic health for older adults, conducted in a community center in Teresina, PI, Brazil. Methods:This is a descriptive study in the form of an experience report, resulting from the participation of undergraduate physical therapy students and physical therapy residents from the Multiprofessional Residency Program in Family Health at the State University of Piauí (UESPI). The activities were carried out with 30 older adults in a community center located in the eastern area of Teresina, PI. The dynamics of the sessions included stretching, warm-up exercises, and a sequence of activities performed before and after the measurement of vital signs. Results: Practices in the community setting strengthened social commitment, a sense of belonging, adherence to regular exercise, functional independence, and reduced exacerbated cardiorespiratory symptoms. Conclusion: The sessions revealed strong participant engagement throughout the activities, recognition of limitations when performing certain exercises, the importance of dialogue, and active listening to participants’ needs. They also emphasized the importance of tailoring activities to the participants’ real-life conditions while respecting their limits. Furthermore, the effectiveness of cardiorespiratory physiotherapeutic interventions in promoting the overall health of the elderly population was observed.